2018
DOI: 10.1186/s40104-018-0250-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of amino acid transporters in the mammary gland from late pregnancy to peak lactation in the sow

Abstract: BackgroundMilk protein is crucial for milk quality in sows and health of newborn piglets. Plasma amino acids (AA) in sows are important precursors for milk protein synthesis in the mammary gland. In order to study the regulation of AA transported in sow mammary glands and possible underlying mechanisms, we measured the expression of genes coding for milk proteins, AA transporter expressions, and plasma AA concentrations in sows at three different physiological stages (D-17, D1 and D17 of lactation), and then f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
(36 reference statements)
4
22
0
Order By: Relevance
“…ATB 0,+ and ASCT1 are significantly increased at peak lactation [ 80 ]. Our lab reported that either EAAC1 or EAAT3 (SLC1A1) is the predominant anionic amino acid transporter and is significantly increased during lactation [ 82 ]. Cationic amino acid transporters CAT-1 , CAT2-B , y + LAT1 and y + LAT2 are widely expressed in the mammary gland and y + LAT2 is significantly increased at peak lactation [ 82 ].…”
Section: Recent Progress In Mammary Gland Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATB 0,+ and ASCT1 are significantly increased at peak lactation [ 80 ]. Our lab reported that either EAAC1 or EAAT3 (SLC1A1) is the predominant anionic amino acid transporter and is significantly increased during lactation [ 82 ]. Cationic amino acid transporters CAT-1 , CAT2-B , y + LAT1 and y + LAT2 are widely expressed in the mammary gland and y + LAT2 is significantly increased at peak lactation [ 82 ].…”
Section: Recent Progress In Mammary Gland Functionmentioning
confidence: 99%
“…Our lab reported that either EAAC1 or EAAT3 (SLC1A1) is the predominant anionic amino acid transporter and is significantly increased during lactation [ 82 ]. Cationic amino acid transporters CAT-1 , CAT2-B , y + LAT1 and y + LAT2 are widely expressed in the mammary gland and y + LAT2 is significantly increased at peak lactation [ 82 ]. Neutral amino acid transporters ASCT1, ASCT2, LAT2 (SLC7A8) and SNAT2 (SLC38A2) are also expressed in the mammary gland [ 82 ].…”
Section: Recent Progress In Mammary Gland Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, the gene expression of LAT1 in the mammary gland is greater than that of LAT2 during the lactation period (19) . The gene expression of LAT2, but not LAT1, is significantly increased with the progression of lactation in sows (21) . In bovine mammary glands, more research has been focused on the effects of LAT1 (20,22) .…”
Section: Branched-chain Amino Acidsmentioning
confidence: 87%
“…These transporters are heterodimeric proteins, which comprise of a catalytic subunit (L-type amino acid transporter 1 (LAT1), encoded by SLC7A5, or L-type amino acid transporter 2 (LAT2), encoded by SLC7A6) and a glycoprotein 4F2 heavy chain (4F2hc). Both LAT1 and LAT2 are highly expressed in the mammary tissues (15) , but which subtype is predominately expressed in the mammary gland seems to be different among species (19)(20)(21) . In rats, the gene expression of LAT1 in the mammary gland is greater than that of LAT2 during the lactation period (19) .…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%